2015
DOI: 10.1016/j.febslet.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Inositol transport proteins

Abstract: a b s t r a c tThe cyclic polyol myo-inositol is a key molecule in many different metabolic pathways among all organisms; in addition, it is fundamental for osmotic balance in the mammalian brain. This review sums up inositol transporters from eukaryotic organisms, elucidating their vital role in regulating the intracellular distribution and uptake of inositol. They can be divided into two groups according to their transport mechanisms: (1) sodium ion coupled inositol transporters that belong to the Solute Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
83
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 113 publications
2
83
0
3
Order By: Relevance
“…The predicted targets included disease resistance proteins, such as RPM1 (hop-miR01/hop-miR39) and TMV resistance protein N (hop-miR33/hop-miR41) and several kinases, which are known to be associated with plant defense mechanisms through signaling-related processes [58, 59]. Novel targets also included several functional proteins, such as PPR-containing protein (required for normal plant development) [60], EMF1 protein (required for floral repression during vegetative development) [61], transporter proteins (such as ABC, inositol transporter 1, USO1) [62], SAND protein (endosomal maturation protein) [63], ARC5 protein (plastid division specifically in mesophyll cells) [64], GLABRA2 (trichome differentiation) [65], TT12 (controlling the vacuolar sequestration of flavonoids in the seed coat endothelium) [65]. Candidate targets of three novel miRNA families, including hop-miR05 and hop-miR47, failed to be annotated.…”
Section: Resultsmentioning
confidence: 99%
“…The predicted targets included disease resistance proteins, such as RPM1 (hop-miR01/hop-miR39) and TMV resistance protein N (hop-miR33/hop-miR41) and several kinases, which are known to be associated with plant defense mechanisms through signaling-related processes [58, 59]. Novel targets also included several functional proteins, such as PPR-containing protein (required for normal plant development) [60], EMF1 protein (required for floral repression during vegetative development) [61], transporter proteins (such as ABC, inositol transporter 1, USO1) [62], SAND protein (endosomal maturation protein) [63], ARC5 protein (plastid division specifically in mesophyll cells) [64], GLABRA2 (trichome differentiation) [65], TT12 (controlling the vacuolar sequestration of flavonoids in the seed coat endothelium) [65]. Candidate targets of three novel miRNA families, including hop-miR05 and hop-miR47, failed to be annotated.…”
Section: Resultsmentioning
confidence: 99%
“…In Trypanosoma cruzi , the etiologic agent of Chagas disease or American trypanosomiasis, myo- inositol transport is facilitated by an energy-dependent, phloridzin-sensitive but cytochalasin B-insensitive system, suggesting that there are at least 2 transporters, a sodium-dependent and a sodium-independent one, that are operational in these parasites (42). Leishmania donovani , the agent of leishmaniasis, transports myo- inositol with a single transporter, L. donovani MIT (LdMIT), with a K m of 0.08 mM (43). Like the fungal transporters, LdMIT is a myo- inositol proton symporter driven by a proton gradient and is expressed at the plasma membrane (22).…”
Section: Discussionmentioning
confidence: 99%
“…Inositol and the management of its levels in the human brain are a focus of investigation for the treatment of neurological disorders like bipolar disease, where it is hypothesized that reduction of cellular signaling via inhibition of myo- inositol biosynthesis or reduction of its cellular concentrations reduces or prevents symptoms (29, 43). Inositol monophosphatase is one putative target for lithium therapy, one of the primary treatments for bipolar disease.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the apical surfaces of the epithelial cells lining the external body tissues, including the skin, fin, gill, and upper regions of the gastrointestinal tract are faced with much greater osmotic challenges as the external osmolality of <5 mosmol/kg H 2 O found in FW is increased to over 1,000 mosmol/kg H 2 O when fish move to SW. As might be expected, epithelial cells in these tissues must accumulate even higher concentrations of organic osmolytes, including inositol, to maintain their cell volume and, consequently, the integrity of the epithelium. Cellular accumulation of inositol can either be the result of secondary active transport across the plasma membrane by the actions of carriers, such as the sodium myo-inositol transporter (SMIT) and/or the proton myo-inositol transporter (HMIT), as has been reported for various mammalian tissues, including the kidney and brain (6, 12, 28, 41), or can be the result of de novo synthesis from glucose 6-phosphate (36, 43). In the mammalian studies so far reported, neuronal tissues appear to accumulate relatively high concentrations of free inositol (20, 46, 47); however, the brain generally expresses relatively low levels of MIPS mRNA (19), suggesting accumulation via SMIT/HMIT may be more physiologically important than de novo synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…IMPA can dephosphorylate both the inositol 3-phosphate that is generated from MIPS activity and also any inositol 1-phosphate that is produced from cell signaling and the turnover of membrane inositol phospholipids (36). Alternatively, in animal cells, the cyclic alcohol can be sequestered as the result of the actions of two types of membrane transporter, the sodium- and the proton-dependent myo-inositol transporters (abbreviated as SMIT and HMIT, respectively) (41), which use the transmembrane sodium or proton gradients to accumulate the metabolite to concentrations of up to 1,000 times that found in the extracellular environment. Adaptation of euryhaline fish to SW or hyper-saline environments has been reported to result in an increase in expression of IMPA in a number of tissues from the eel (24, 25), killifish (45), and tilapia (15, 24, 25, 39, 44).…”
mentioning
confidence: 99%